Technique to Distinguish Tracks of Leopard and Tiger Cub - Sagar, S. R.; Singh, L. A. K. (Indian Forester, 1990)
The stride of a large cat in its normal walk is the distance from the tip of the impression or the pad of a hind limb to the corresponding position at an adjacent impression of the same pug. The stride is also approximately twice the distance between two adjacent pug marks, that of the left and right hind limbs during normal walk, and approximately thrice during a short pace gait. It is concluded from the present study that the strides of adult leopard were mostly above 90 cm while that of young tigers were 70-85 cm. These observations have formed the basis to distinguish the tracks of a leopard and a young tiger, both of which may have a pug mark length of 8-9 cm.